THE DEVELOPMENT OF BILINGUAL ENGLISH TEACHING MATERIAL ON THE PART OF BODY FOR THIRD GRADE STUDENTS AT SD DWIJENDRA DENPASAR - Komang Juniantara; I Gusti Ayu Indah Triana Juliari (Widyasrama, 2021)
This research aims to Develop English learning material to support online learning activities during the pandemic for third grade students at SD Dwijendra Denpasar. This research applied qualitative & quantitative design. Researcher use questionnaires and scoring rubric to get student opinions and experience in learning the bilingual English material and also validity from expert judges for the development of teaching materials before its ready to use for students. The result showed the English teaching materials on the part of body is ready to use after the validation from the expert judges and based on the questionnaires could conclude that this teaching material had very good quality. Therefore, this teaching material was proper to be used in English teaching learning process for third grade students in SD Dwijendra Denpasar.